The Evaluation of the Affect of Seventh Staging System of Esophagus Cancers to the Prognosis and Survival - Pi̇rzi̇renli, M.G.; Taslak Şengül, A.T.; Büyükkarabacak, Y.; Başoǧlu, A. (Ondokuz Mayis University, 2024)
The exact staging of esophagus cancers are very important for the planning of treatment and analyse of prognosis. The aim of our study is the evaluation of last staging criteria of esophagus cancers and the comparison of sixth and seventh TNM staging systems. The eighty five patients who underwent resection due to esophagus cancer in the Thoracic Surgery Department of 19 Mayıs University, Faculty of Medicine between January 2003 and December 2014 were evaluated retrospectively. The clinical staging and the factors that effects the survival are evaluated both by the 6th and 7th TNM by using radiological imaging and upper gastrointestinal system endoscopy. The postoperative mean survival time is evaluated as 44.46 ± 6.71 months is measured for 85 patients who were resected by the diagnosis of esophagus cancer. The most common cause of admission to the hospital are dysphagia and weight loss. The 76.5 % of the patients are squamous cell carcinoma and 23.5 % of the patients are adenocarcinoma as a histopathological diagnosis of cancer. The most highest postoperative survival (57. 50 ± 27.86 months) is reported after the McKeown surgery. According to the seventh staging system the tumor depth, the number of metastatic nodes and metastasis affect the postoperative prognosis and ratio of survival negatively.It is showed that the effected lymph nodes and the number of effected lymph nodes are the most valuable criterias in the seventh TNM staging system and it is evaluated that more powerful results are gained when it is compared with the sixth TNM staging system. © 2024 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: Esophagus Cancer; Resection; Stage; Survival